Dissecting the single-cell transcriptomeunderlying chronic liver injury - Junjun Wang; Wei Hu; Zhenyang Shen; Teng Liu; Weiming Dai; Bo Shen; Xiaoman Li; Jingni Wu; Lungen Lu; Shengli Li; Xiaobo Cai (Elsevier, 2021)
Chronic liver disease (CLD) is currently a major health problem worldwide, which is accompanied by chronic liver injury and lack of clinically effective treatment; however, systematic characterization of chronic liver injury procedures at single-cell resolution is lacking. In the present study, we established chronic liver injury mouse models and conducted single-cell RNA sequencing (scRNA-seq), including choline-deficient, ethionine-supplemented (CDE) and 3,5-diethoxycarbonyl 1,4-dihydrocollidinen (DDC) mouse models. We captured in total 16,389 high-quality cells and identified 12 main cell types in scRNA-seq data. Macrophages and endothelial cells are the largest cell populations in our dataset. Transcriptional trajectory analysis revealed different expression patterns of cells between CDE and DDC models and identified potential liver injury markers, such as Ets1, Gda, Itgam, and Sparc. Differential analysis identified 25 and 152 differentially expressed genes in CDE and DDC macrophages, respectively. In addition, 413 genes were detected to exclusively express in specific pseudotime states of macrophages. These genes were found to participate in immune-related biological processes. Further cell-cell communication analysis found extensive receding of cell-cell interactions between different cell types in the liver injury process, especially in the DDC model. Our study characterized the single-cell transcriptional landscape in the process of chronic liver injury, promoting the understanding of the underlying molecular mechanisms and providing candidate clinical strategy for effective intervention of chronic liver diseases.